Main performance results of the EDEN ISS rack-like plant growth facility - Boscheri, Giorgio; Volponi, Marco; Lamantea, Matteo; Lobascio, Cesare; Schubert, Daniel; Zabel, Paul (2017)
Plant cultivation in large-scale closed environments is challenging and several key technologies necessary for space-based plant production are not yet space-qualified or remain in early stages of development. The Horizon2020 EDEN ISS project aims at development and demonstration of higher plant cultivation technologies, suitable for near term deployment on the International Space Station (ISS) and from a long-term perspective, within Moon and Mars habitats. The EDEN ISS consortium, as part of the performed activities, has designed and built a plant cultivation system to have form, fit and function of an European Drawer Rack 2 (EDR II) payload, with a modularity that would allow its incremental installation in the ISS homonymous rack, occupying from one-quarter rack to the full system. The construction phase is completed, and the developed system is being tested in a laboratory environment, planned for further validation at the highly-isolated German Antarctic Neumayer Station III, in a container-sized test facility to provide realistic mass flow relationships and interaction with a crewed environment. This paper describes the system as built and the key results of the first ISPR plant growth facility laboratory tests.